(3cJGH fZeI GdHjGf aj JaSjQ GdbQBfs - (3TgGH GdOjf YeQ Hf eMehO GdSgQhQOj,J (B632 (3g` s ((3fhQ GdOjf GdeQUai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ChOY cJGHg GdYRjR HhGdZ GdMce hSejJg fZHI GdHjGf ai JaSjQ GdbQBf hGddg GdeCehd Cf jfaY Hg hjKjH Ydjg bhdg JYGdi HSe Gddg GdQMef GdQMje ajg GNJUGQ cCfg bGd EHOGA HSe Gddg s
(3BNQgG (B:s
(3bhdg JYGdi (B( (3jhShS ai UOhQ GdfGS (B) (3Ci GdcdGe GdNai GdPi jUd eagheg Edi GdbdH ef ZjQ SeGY hgh ef GdLfI bjd Cf bd gh Gddg CMO hGdeYhPJjf OhGA ef cd OGA hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs